2019
DOI: 10.1016/j.scs.2018.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Source identification of total petroleum hydrocarbons and polycyclic aromatic hydrocarbons in PM10 and street dust of a hot spot for petrochemical production: Asaluyeh County, Iran

Abstract: Total petroleum hydrocarbons (TPH) and polycyclic aromatic hydrocarbons (PAHs) are important pollutants that affect public health in urban areas, especially in developing and oil-rich countries such as Iran. This assesses the relationship between TPH and PAHs in street dust and suspended dust, and investigates toxicity level in the urban environment of the most important petrochemical center in Iran. For this purpose, 21 and 48 street dust samples were collected for TPH analysis and PAH analysis, respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…Ansari et al [55] found that indoor PAHs mainly originated from cooking fuel in rural India such as wood. Abbasi et al [56] showed that indoor PAHs may come from petroleum in developing and oil-rich countries such as Iran. So the source of PAHs in indoor dust is related to the local industrial structure and the lifestyle of residents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ansari et al [55] found that indoor PAHs mainly originated from cooking fuel in rural India such as wood. Abbasi et al [56] showed that indoor PAHs may come from petroleum in developing and oil-rich countries such as Iran. So the source of PAHs in indoor dust is related to the local industrial structure and the lifestyle of residents.…”
Section: Discussionmentioning
confidence: 99%
“…Dermal contact and ingestion exposures are also important route for children and are associated with behaviors such as crawling on the floor and contact with dirt and grass [59] . In addition, early development of organ, nervous, and immune systems may enhance the carcinogens sensitivity in children [56] . However, the results calculated based on ILCRs model still have certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…It is a group of more than 10,000 compounds, but the National Institute of Standard and Technology (NIST) reported 660 structural formulas of PAHs in NIST Special Publication 922/2011 (Kubiak 2013). PAHs are formed by incomplete combustion of many types of fuels, particularly diesel fuel (Abbasi and Keshavarzi 2019). When they are adsorbed on suspended particulate matter, they are one of the main components of smog.…”
Section: Pahs and Their Oxidized Formsmentioning
confidence: 99%
“…The word 'smog' comes from a combination of two English words -smoke and fog (Schwartz Cowan 1997). This is an unnatural phenomenon, formed mainly due to windless weather -artificial fog composed of residues after incomplete combustion of many types of fuels (Abbasi and Keshavarzi 2019). The main component of smog is suspended particulate matter, defined as aerosols of liquid drops or solid particles.…”
Section: Introductionmentioning
confidence: 99%
“…According to the meteorological statistics of Mashhad in 2018, the months of June (25.5 •C), July (30.17 •C) and August (28.7 •C) had the highest temperature and the minimum rainfall was in the three months of summer. In these seasons of the year, a lack of rainfall and high temperatures cause a decrease in soil moisture, resulting in the suspension of soil particles due to wind and a rise in dust and suspended particles (Abbasi &Keshavarzi 2019). In addition, according to Mashhad's annual report on environmental pollutants for 2018, the rst half of the year saw higher levels of PM 10 .…”
Section: Spatial Distribution and Source Identi Cation Of Pahsmentioning
confidence: 99%